Higher risk of carotid plaque among lean individuals with non-alcoholic fatty liver disease: A retrospective study - Jiangfeng Xue; Lun Zhao; Liang Shao; Huiwang Zhang; Yewei Feng; Ping Shuai (PLoS ONE, 2025)
Background Lean individual with non-alcoholic fatty liver disease (L-NAFLD) is a prominent area of research, yet its pathogenesis and association with other diseases such as atherosclerotic cardiovascular disease remain uncertain. Object A retrospective study, investigate the association between non-alcoholic fatty liver disease (NAFLD) and carotid plaque (CP) in lean [body mass index (BMI) <24Kg/m2] and non-lean (BMI≥24Kg/m2) populations, as well as identify the related influence factors. Method 3,587 participants were eligible and categorized into 4 groups based on the presence with CP and BMI, binary logistic regression analysis was utilized alongside other statistical methods. Results L-NAFLD participants had a 1.395-fold higher risk of CP compared to lean individuals without NAFLD. Age, gender, systolic blood pressure, low-density lipoprotein cholesterol, fasting blood glucose, and Fibrosis-4 index (FIB-4) were identified as independent risk factors with cutoff values lower than the normal upper limits. However, this association was not observed among non-lean participants, regardless of confounding factors adjustment. Moreover, the impact of FIB-4 on the association of NAFLD and CP was more significant in lean CP participants (OR = 1.360 for 1.30 ~ 2.67, and OR = 2.002 for >2.67~<3.48) than in non-lean CP ones. Conclusion The L-NAFLD population had a higher risk of CP, while lean CP individuals experienced more severe liver fibrosis. Implementing stricter management of risk factors may improve the health status of high-risk populations.